ANALISIS GANGGUAN PERTUMBUHAN BATITA BERDASARKAN ANTOPOMETRI DI WILAYAH CILACAP TENGAH - Tri Budiarti; Titin Kartiyani; Susanti Susanti (KOLONI, 2022)
Infancy and toddlerhood even since in the womb are a golden period. If in infancy and toddlerhood, the growth and development of toddlers is not properly monitored and is impaired, it is likely that it will not be able to be repaired in the next period. Therefore, it is necessary to carry out routine growth monitoring on the growth of toddlers so that they can be detected if there are growth irregularities. In the area of ​​Cilacap Tengah 1 Public Health Center, there were 122 cases of malnutrition, and 8 cases of malnutrition. Malnutrition data collection in Cilacap Regency is based on 2 categories, namely the indicator comparing weight with age (BB/U) and the second category is comparing weight with height (BB/TB). This study aims to determine the analysis of growth disorders based on anthropometry. The research method used a cross sectional design with a simple random sampling technique using primary and secondary data at the Posyandu in the Central Cilacap Region as many as 57 parents who had children according to the criteria. Furthermore, the data were analyzed using the chi square test and it was concluded that only infection had a relationship with growth disorders. Meanwhile, nutritional intake, parenting, stimulation, the economy of parents, and the environment have no relationship with growth disorders. Keywords: growth disorders, anthropometry